2001
DOI: 10.1007/s00232-001-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Region Critically Involved in the Interaction of Phlorizin with the Rabbit Sodium-D-Glucose Cotransporter SGLT1

Abstract: In order to define potential interaction sites of SGLT1 with the transport inhibitor phlorizin, mutagenesis studies were performed in a hydrophobic region of loop 13 (aa 604-610), located extracellularly, close to the C-terminus. COS 7 cells were transiently transfected with the mutants and the kinetic parameters of alpha-methyl-D-glucopyranoside (AMG) uptake into the cells were investigated. Replacement of the respective amino acids with lysine reduced the maximal uptake rate: Y604K showed 2.2%, L606K 48.4%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 13 publications
3
33
1
Order By: Relevance
“…These cells have been shown in previous studies to lack endogenous Na ϩ -dependent glucose transport (6,16). All of the mutant clones showed lower AMG uptake rates, which might be due to insufficient sorting into the plasma membrane, inappropriate conformational structure of the expressed SGLT1 in the plasma membrane and/or a global reorganization of the disulfide bonds.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These cells have been shown in previous studies to lack endogenous Na ϩ -dependent glucose transport (6,16). All of the mutant clones showed lower AMG uptake rates, which might be due to insufficient sorting into the plasma membrane, inappropriate conformational structure of the expressed SGLT1 in the plasma membrane and/or a global reorganization of the disulfide bonds.…”
Section: Discussionmentioning
confidence: 76%
“…Transient transfection was performed by using the activated dendrimer transfection reagent SuperFect TM (Qiagen) as described earlier (16). The efficiency of transfection was tested in COS-7 cells that were simultaneously transfected with the pHook TM -2lacZ control plasmid expressing ␤-galactosidase under identical conditions (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, end-tags with six histidines were added at both sides of the loop. The initial immobilization experiments done with a mixture of POPC and DOGS-Ni 2ϩ -NTA gave a strong indication for the expected interactions between His 6 -tagged loop 13 and Ni 2ϩ -NTA via the Ni 2ϩ -NTA/ His 6 system, as EDTA could prevent immobilization. Removal of the loop by competition with imidazole, which usually disrupts such interactions, failed, however; hence, additional interactions between the phospholipids and other parts of the peptide had to be assumed.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we have shown that phlorizin binds to loop 13 of rabbit SGLT1 (aa 541-638) via the aromatic aglucone moiety inducing conformational changes of the loop, predominantly in the region between aa 600 and aa 621 (4,6) of the C terminus. Mutagenesis experiments provided also data on individual amino acids critically important for the interaction with the inhibitors (6,13,14).…”
mentioning
confidence: 99%
“…Previous studies by our groups have shown that, in rbSGLT1, loops 13-14 facing the extracellular space is critically involved in the binding of the aglucon (64). In vitro studies suggest that the loop has a substructure of two small helices and interacts in several regions with membrane phospholipids (10,65).…”
Section: Sglt1 Sensorsmentioning
confidence: 94%